Carbon sequestration scenarios in Continental Portugal - Cunha, Jorge (2019)
Cunha, J., & Cabral, P. (2019). Carbon sequestration scenarios in Continental Portugal: Which way to go forward?. 315. Abstract from 15th European Ecological Federation (EEF) Congress and 18th National SPECO Meeting, Lisboa, Portugal.